Fraud Hexagon and Fraudulent Financial Reporting in ASEAN Islamic Banks: Evidence from Indonesia, Malaysia, Brunei Darussalam, and the Philippines - Nani Wahyuni; Taufik Akbar (The Indonesian Accounting Review, 2026)
Fraudulent financial reporting in Islamic banks remains an important concern because Sharia compliance does not automatically eliminate governance weaknesses and managerial opportunism. However, empirical evidence on the determinants of fraudulent financial reporting in ASEAN Islamic banks using the Fraud Hexagon framework remains limited. This study aimed to examine the effect of the Fraud Hexagon factors on fraudulent financial reporting in Islamic banks across Indonesia, Malaysia, Brunei Darussalam, and the Philippines during 2020–2024. Using a quantitative explanatory design, this study analyzes 152 bank-year observations based on audited annual reports. Fraudulent financial reporting is proxied by the F-Score, while the independent variables consist of growth pressure, effective monitoring, related-party sales, CEO education background, CEO tenure, and corporate involvement in government projects. The data were analyzed using partial least squares–structural equation modeling (PLS-SEM). The results show that CEO tenure has a significant positive effect on fraudulent financial reporting (β = 0.330, p < 0.001), while effective monitoring also has a significant effect (β = 0.178, p = 0.021). The model explains 16.5% of the variation in the F-Score. These findings imply that Islamic banks should strengthen governance mechanisms, evaluate long executive tenure, and improve monitoring effectiveness to reduce fraudulent financial reporting risk.